Lupus Eritematosus Sistemik pada Pria - Zikry Aulia Hidayat (Faculty of Medicine, Universitas Andalas, 2020)
Objective: Systemic lupus erythematosus (SLE) is a complex autoimmune disease involving many systems. Highest incidence and prevalence of SLE is found in Northern America 23.2/100,000 population/year and 241/100,000 population. According to sex differences, SLE is predominantly occurs in women than men with ratio 15:1 to 22:1. This discrepancy often causes delay in diagnosing SLE in male patients. Method: Case report. Result: We reported a male patient aged 21 years with pain of his joints, hyperpigmentation lesions on his face, alopesia, oral ulcers and decrease of body weight. Laboratory results showed increases in AST, ALT and D-Dimer, and from ANA Profile examination we got several positives results such as RNP/Sm (RNP/Sm) (++), Sm (Sm) (+), Ro-52 recombinant (52) (+), PCNA (PCNA) (+), DsDNA (DNA) (+), Nucleosome (NUC) (+), Histone (HI) (++), Ribosomal-P-protein (RIB) (+++) dan AMA-M2 (M2) (+). This patient met SLE criteria based on ACR 1997, SLICC 2012 and EULAR/ACR 2018. Patient was given oral methyl prednisolone 16-16-8 mg and VTE prophylaxis with subcutaneous heparin 2x5000 IU. Conclusion: SLE occurs rarely in male patients than female patients and has more diverse manifestations.